2018
DOI: 10.3390/ijerph15040643
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Suicide Bereavement on Educational and Occupational Functioning: A Qualitative Study of 460 Bereaved Adults

Abstract: People bereaved by suicide are at an increased risk of suicide and of dropping out of education or work. Explanations for these associations are unclear, and more research is needed to understand how improving support in educational or work settings for people bereaved by suicide might contribute to reducing suicide risk. Our objective was to explore the impact of suicide on occupational functioning. We conducted a cross-sectional online study of bereaved adults aged 18–40, recruited from staff and students of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 32 publications
(52 reference statements)
0
50
0
Order By: Relevance
“…As a result of the psychological trauma experienced by the survivors, many reported ongoing thoughts of suicide and remain a potential risk of suicide in the future. Previous research supports the finding that traumatic events and symptoms of vulnerable psychological health such as depression, extreme grief, anxiety, and obstacles to leading a normal life, have the potential to lead to suicidal deaths [28,43,44,45]. This study further revealed that the Rana Plaza building lacked enough available safety exits and stairs, and the exits that were available were blocked by clothing materials limiting the number of people who could escape the building leading to an increase in loss of life.…”
Section: Discussionmentioning
confidence: 73%
“…As a result of the psychological trauma experienced by the survivors, many reported ongoing thoughts of suicide and remain a potential risk of suicide in the future. Previous research supports the finding that traumatic events and symptoms of vulnerable psychological health such as depression, extreme grief, anxiety, and obstacles to leading a normal life, have the potential to lead to suicidal deaths [28,43,44,45]. This study further revealed that the Rana Plaza building lacked enough available safety exits and stairs, and the exits that were available were blocked by clothing materials limiting the number of people who could escape the building leading to an increase in loss of life.…”
Section: Discussionmentioning
confidence: 73%
“…The reasons for these associations are unclear but quantitative studies comparing scores on dimensions of grief find that people bereaved by suicide report higher scores on rejection, shame [8], and perceived stigma compared to those bereaved by other unnatural deaths [12]. Qualitative research also suggests that the social awkwardness of friends and colleagues contributes to difficulties with social and occupational functioning [11,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Proactively seeking formal and informal support can also be hampered by physical and psychosomatic health manifestations of grief, including low energy, poor appetite and insomnia (Hoffmann, Myburgh, & Poggenpoel, 2010;McKinnon & Chonody, 2014). Previous research also indicates educational and employment functioning can be hampered due to lack of institutional support, poor concentration levels due to grief and socially withdrawing from others for fear of stigmatisation (Pitman, Khrisna Putri, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%